Doxycycline Usage for Prevention of Leptospirosis among Farmers and Reasons for Failure to Use Chemoprophylaxis: A Descriptive Study from Southern Sri Lanka - C. L. Fonseka; B. N. Vidanapathirana; C. M. de Silva; A. A. B. B. Athukorala; P. R. Goonawardena; A. P. Karunathilake; I. H. Rajapakse; A. S. Dissanayake (Journal of Tropical Medicine)
Background. Leptospirosis causes substantial morbidity and mortality in Sri Lanka. Health authorities have implemented a chemoprophylaxis programme for prevention of disease for farmers who are at a high risk of leptospirosis. Only 39% of general population is aware of chemoprophylaxis. Awareness on chemoprophylaxis and its usage among the risk population and the reasons for non-usage was uncertain. Our aim was to assess the chemoprophylaxis usage for prevention of leptospirosis among farmers and reasons for failure to use such preventive strategy. Methods. Cross-sectional descriptive study was conducted on farmers in community setting in Galle District. Multi-stage cluster sampling method was used. Out of the seventeen “Ministry of Health” (MOH) divisions within the Galle district, nine divisions were randomly selected and, subsequently, two subdivisions (“Public Health Midwife” divisions) were randomly selected from each MOH division. From each PHM division (total of 18), a cluster who does farming as the main source of income was selected. From these farmers, details on demographics, knowledge on leptospirosis and knowledge and practice on chemoprophylaxis usage were obtained through an interviewer administered open-ended questionnaire. From those who have not properly taken chemoprophylaxis, the reasons for non-usage were explored by semistructured interviews. Results. We recruited 319 (77%-males) farmers to the study. Eighteen (5.6%) have already had leptospirosis. Majority (86.8%) of farmers were aware that doxycycline can be used to prevent the disease occurrence. Only 31% knew about correct recommendations of chemoprophylaxis usage adopted by the national guidelines. Only 28.5% (91) used doxycycline prophylaxis. Out of those, only 60 farmers (65.9%) continued the prophylaxis throughout the contact and followed national recommendations. Themes responsible for non-usage were elicited such as lack of awareness of chemoprophylaxis usage, false sense of security from the disease by perceived “immunity” due to prolong exposure or due to low prevalence of disease, lack of motivation, lack of availability of medication, and fear of side effects. Conclusions. Awareness of leptospirosis is better among farmers compared to the general population. Usage of chemoprophylaxis among farmers was highly inadequate. Individual and health system related hypotheses and myths exist for non-usage of chemoprophylaxis. Thus, an urgent concerted campaign aimed at increasing awareness within the target group through education and making medicines effectively distributed is essential for better prevention of the disease.